AI Catalyst: Revolutionizing Workforce Development - A Comprehensive Study of Intelligent Learning Systems - Lhakard, Polwasit (Cita Konsultindo Research Center, 2024)
This comprehensive study investigates the transformative impact of Artificial Intelligence (AI) on employee training and development through an extensive review of theoretical frameworks and case studies. The research explores how AI technologies are reshaping traditional training paradigms, enabling personalized learning experiences, and enhancing organizational performance. Through qualitative analysis of secondary data and content analysis of case studies, the study investigates the implementation challenges, benefits, and future prospects of AI in corporate learning environments. Findings reveal significant improvements in training effectiveness, learner engagement, and skill acquisition rates through AI integration. However, the research also highlights concerns regarding data privacy, ethical considerations, and the need for human oversight in AI-driven training systems. The study concludes by proposing a framework for the ethical and effective integration of AI in organizational learning strategies, contributing to the growing body of knowledge on AI in human resource development.